Qualidade da água superficial e aspectos do sistema ambiental da bacia hidrográfica do rio Salobra, Serra da Bodoquena-MS - DAIRES EDUARDO BENTO LIMA FRANCO (2022)
Besides having an important role for life maintenance in the aquatic environment, the water also performs a fundamental function for the terrestrial environment, supporting the human life, the animals and plants. Therefore, the analysis of the water physical, chemical and biological characteristics is essential so that we can know the situation of the hydric bodies. Due to the relevance of the water study, the survey area is situated in the region of Bodoquena mountains, in the transition between the “Cerrado” and “Pantanal” in the state of Mato Grosso do Sul, having a rich biodiversity and geodiversity. The river basin reaches the rural areas of the municipalities of Porto Murtinho, Bonito, Bodoquena and Miranda and part of the urban area of Bodoquena- MS. The survey had the goal of analyzing the environmental system of Salobra river basin, considering the physico-environmental aspects and the quality of the superficial water. A qualitative and quantitative analysis was made through the description and interpretation of the literature data, land use characterization and vegetation cover as well as the analysis of the results of the physical, chemical and biological parameters of superficial waters. The survey results showed that the dissolved oxygen parameters, total nitrogen, total coliforms and thermotolerant coliforms presented values above the limit allowed by the legislation, fact that is giving cause for concern about the river environment in the ecological aspect. The identification of the environmental degradation process in the river basin highlights the necessity of intervention in the area for reducing the environmental impacts with environmental conservation actions and accordance with the legislation considering the vulnerability and importance of Serra da Bodoquena area and the influence in Pantanal.